A Cross-Language Study of Tonal Variants in Mandarin in Different Attentional Conditions - Xin Chen; Jianqin Wang; Ji Lu (Behavioral Sciences)
This study used an electrophysiological technique to investigate the perception mechanism of Mandarin native speakers and learners from non-tonal language backgrounds when processing the third tone (T3) and its variants in Mandarin. The experiments used a 2 × 2 two-factor mixed design to examine the perception of T3 and its variants and the processing mechanisms of learners and native speakers under different levels of attention. Differences in attention and language backgrounds in the perception of Mandarin tones were further investigated. These results provide evidence that there are no significant differences in the perception of the two T3 variants by native Mandarin speakers under different attentional conditions. In contrast, learners from non-tonal language backgrounds were more likely to perceive a low flat tone as T3 than a low concave tone in the attentive condition. This means that learners are more likely to rely on low-pitch cues rather than the concave contour of the tone when perceiving T3.